ORTHOTIC INFLUENCE OF LOCOMOTION AND VERTICALIZATION OF MYELOMENINGOCELE - Katarína Šromovská (Acta Tecnología, 2017)
The thesis explains orthotic influence of myelomeningocele – spine bifida, which depends on age, damage level and patient’s disease. The main goal of this thesis is to evaluate the influence and effect of orthoses on patient’s image of walking. HKAFO orthosis (an orthosis influencing the hip, knee and ankle joints and the foot) is designated for patients in need of stabilization or compensation, when the lower limb is paralyzed, but the strength of hip and partially of knee extensor is kept, or when the lower limb is completely paralyzed. Correct type of RGO allows the patient to walk faster and with less energy consumption. The goal of the orthosis application is verticalization in the most possible physiological standing and locomotion.